Boosting Employee Performance: The Role of Commitment, Job Satisfaction and Engagement - Iswahyudi, Rudy; Suyono, Joko; Suyono, Aldrin Arizona; Elisabeth, Damarsari Ratnasahara (Universitas Muhammadiyah Gresik, 2025)
This study aims to analyze the influence of organizational commitment, job satisfaction, and employee engagement on employee performance at PT XYZ, an electronic cigarette company in Malang. This research is motivated by previous studies that have shown inconsistent findings regarding the influence of these three variables on employee performance. A quantitative approach with a saturated sampling technique involving 90 back-office employees was employed. Data were collected through questionnaires, and the validity and reliability were tested using SPSS 23.00. The Normality test, Heteroscedasticity, Multicollinearity, and Autocorrelation tests showed that the regression model had meet all classical assumptions. Meanwhile, data analysis using Regression analysis showed that simultaneously the three independent variables had a significant effect with a calculated F value of 32.504 and a significance of 0.000. Partially, organizational commitment, job satisfaction, and employee engagement each had a significant effect on employee performance with a significance value of 0% or below the tolerance value of 5%. Regression analysis showed that organizational commitment, job satisfaction, and employee engagement significantly influenced employee performance, both simultaneously and individually. The coefficient of determination (R²) of 0.739 indicates that 73.9% of the variation in employee performance is explained by these three variables, with organizational commitment being the most dominant variable. This study provides empirical evidence that organizational commitment, job satisfaction, and employee engagement are crucial and interrelated factors contributing to improved employee performance.